The Impact of Russian-Ukrainian War towards Abnormal Stock Return And Trading Volume Activity - Andre Putra Pratama; Saiful Bahri (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
This study aims to determine the impact of the events of the Russian and Ukrainian wars by looking at market reactions using 2 measurement variables, namely Abnormal Return and Trading Volume Activity. This study uses a quantitative approach with secondary data taken from the IDX and Yahoo Finance websites. The population in this study were energy sector companies that were listed on the Indonesian Stock Exchange before the events of the Russian and Ukrainian wars on February 24, 2022. Meanwhile, the sample used in this study were energy sector companies that met predetermined criteria totaling 34 companies. Data collection techniques in this study used literature and documentation. Meanwhile, data analysis techniques used paired sample t-test and Wilxocon signed rank t-test. The results of this study indicate that (1) There are significant differences in the Average Abnormal Return (AAR) of energy sector companies listed on the Indonesia Stock Exchange in the period before and after the Russian and Ukrainian wars. (2) There are significant differences in the Average Trading Volume Activity (ATVA) in energy sector companies listed on the Indonesia Stock Exchange in the period before and after the Russian and Ukrainian wars.